2020
DOI: 10.1177/1757975920963889
|View full text |Cite
|
Sign up to set email alerts
|

A pilot project: handwashing educational intervention decreases incidence of respiratory and diarrheal illnesses in a rural Malawi orphanage

Abstract: Children who live in orphanages represent a population particularly vulnerable to transmissible diseases. Handwashing interventions have proven efficacy for reducing the rate of transmission of common infectious diseases. Few studies have analyzed the delivery of health interventions for children in orphanages in sub-Saharan Africa. To address this gap, we conducted an ecological assessment and piloted a handwashing intervention in an orphanage in rural Malawi, focusing on caregiver knowledge and behaviors, ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This study revealed that there was a 45% (IRR: 0.55, 0.48, 0.61, P < 0.001) reduction of CHDincidence among households intervened with handwashing with soap at critical times, which is constituent with previous ndings reported a 42-47% reduction [31]. Another nding from Pakistan indicated a 53 %, diarrhea reduction [32] and a 33% in Malawi [33] despite the level of reduction varied. The variation in reduction might be due to caregivers' handwashing practices and knowledge on diarrhea prevention.…”
Section: Discussionsupporting
confidence: 76%
“…This study revealed that there was a 45% (IRR: 0.55, 0.48, 0.61, P < 0.001) reduction of CHDincidence among households intervened with handwashing with soap at critical times, which is constituent with previous ndings reported a 42-47% reduction [31]. Another nding from Pakistan indicated a 53 %, diarrhea reduction [32] and a 33% in Malawi [33] despite the level of reduction varied. The variation in reduction might be due to caregivers' handwashing practices and knowledge on diarrhea prevention.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, the age and the education of the mother, the type of toilet facilities, non-exclusive breastfeeding and bottle feeding were also risk factors for diarrhea in children [24] . A clinical trial showed a significant reduction in parasite detection rates following water, sanitation, and hygiene interventions [25,26] . Fang et al had reported three high endemic regions of infectious diarrhea in Jiangsu Province from 2013 to 2017, which were Xuzhou, Yancheng and the border area between Wuxi and Suzhou [27] .…”
Section: Discussionmentioning
confidence: 99%
“…While the 5‐step strategy is a promising strategy to improve in school‐going children, there is limited information regarding school‐going children and the use of a five‐step handwashing technique among kindergarten children globally. In Malawi, assessments regarding hand hygiene have focused on different populations (adults) (Rissman et al, 2020 ; Sheth et al, 2010 ; Slekiene & Mosler, 2020 ). Therefore, it is essential to evaluate hand hygiene knowledge and demonstrated technique before and after the implementation of a hand hygiene programme and its sustainability among kindergarten students in Malawi.…”
Section: Introductionmentioning
confidence: 99%